2008
DOI: 10.1016/j.jmb.2008.02.046
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Energy Landscape of Repeat Proteins using NMR-detected Hydrogen Exchange

Abstract: Repeat proteins contain tandem arrays of a simple structural motif. In contrast to globular proteins, repeat proteins are stabilized only by interactions between residues that are relatively close together in the sequence, with no "long-range" interactions. Our work focuses on the tetratricopeptide repeat (TPR), a 34 amino acid helix-turn-helix motif found in tandem arrays in many natural proteins. Earlier, we reported the design and characterization of a series of consensus TPR (CTPR) proteins, which are buil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
40
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 45 publications
9
40
1
Order By: Relevance
“…Such a description implies that thermodynamically, individual repeats unfold independently of each other and thus can populate partially folded configurations. This observation was confirmed when Cortajarena et al used equilibrium, NMR-detected hydrogen/deuterium exchange to observe sequential unfolding transitions for 2 CTPR proteins containing 2 and 3 repeats, respectively (20). However, we have also previously shown that kinetic folding of these 2 proteins at 20°C was 2-state over the limited denaturant concentration range measured (23).…”
Section: Biophysics and Computational Biologysupporting
confidence: 73%
See 2 more Smart Citations
“…Such a description implies that thermodynamically, individual repeats unfold independently of each other and thus can populate partially folded configurations. This observation was confirmed when Cortajarena et al used equilibrium, NMR-detected hydrogen/deuterium exchange to observe sequential unfolding transitions for 2 CTPR proteins containing 2 and 3 repeats, respectively (20). However, we have also previously shown that kinetic folding of these 2 proteins at 20°C was 2-state over the limited denaturant concentration range measured (23).…”
Section: Biophysics and Computational Biologysupporting
confidence: 73%
“…Our analysis shows that the modular multistate equilibrium folding of the CTPRa proteins (20,23,38) is also observed in their kinetic folding and unfolding. Excitingly, our results are also completely consistent with the 2 computational studies on the folding CTPR proteins.…”
Section: Comparison Of Kinetics With Equilibrium and Computational Stmentioning
confidence: 71%
See 1 more Smart Citation
“…Thus, although it has been shown that at equilibrium CTPRan and CTPRn proteins have the propensity for multistate folding and the population of stable intermediates, 23,24,36 our data show that this observable multistate folding can be modulated and is determined by the total stability of the protein and, consequently, the stability of the remaining partially folded species under the unfolding conditions. If they are unstable the protein acts as an observably two-state unfolding system (e.g., CTPRa2 and CTPRa3), with intermediates being high-energy and not populated.…”
Section: Discussioncontrasting
confidence: 55%
“…11,12,17 NMR and equilibrium chemical denaturation studies on the CTPR2 and CTPR3 proteins suggest that, despite the apparent cooperative equilibrium unfolding, intermediate states with frayed terminal helices are populated through the denaturation transition. 23,24 Further, Regan and coworkers have used DSC to show that all the CTPRa proteins undergo multistate equilibrium folding under their conditions. 20 This multistate folding was elegantly described by fitting and modeling the thermodynamic unfolding transition of chemical denaturations to these repeat proteins using a homozipper Ising model.…”
Section: Introductionmentioning
confidence: 99%